Emergency Surgery in A Tertiary Hospital: The Covid-19 Experience (Bangladesh Journal of Medical Science, 2020)
Objective: Evaluate the impact of Covid-19 in a critical area and analyze the changes in the daily activities in an Emergency Department of a tertiary COVID-Hospital.Methods: We reported and compared the surgical procedures performed for acute appendicitis and acute cholecystitis between two periods (March and April 2019 and March and April 2020) at Emergency Surgery Department of Parma University Hospital, a tertiary COVID-Hospital.Results: A total of 72 patients underwent surgery between March and April 2019 and 36 between March and April 2020 for acute appendicitis and cholecystitis. The average length of stay was comparable in the two considered years for LA (4.23±1.69 days in 2019 versus 4.5±2.33 days in 2020). The average length of stay in patients with acute cholecystitis was 5.9±3.8 days in 2019 and 8.23±5.5 days in 2020(P=0.038). The average hospitalization was comparable with 2019 data (5.62±3.77 days)n March 2020;whereas, April 2020 was statistically significantly longer 10.5±6 days (P= 0.023).Conclusions: Half of the emergency centers reported a drop in the overall number of urgent cases as confirmed in our department, where the number of total appendicectomy and cholecystectomy was halved comparing the two months in 2019 and 2020, 72 operations in 2019 versus 36 operations in 2020.During the pandemic, the confidence of the population to the healthcare systems was poor, and this can explain the delayed access to the emergency department of patients who suffered from an acute illness.Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 66-S 68